A STRESS MANAGEMENT INTERVENTION FOR SECONDARY TEACHERS - Ugwuanyi, Christian Sunday (JIP (Jurnal Intervensi Psikologi), 2023)
Several studies have reported the prevalence of stressors and work- related conditions among educators in Nigerian school environments, but there are limited reports on the coping mechanisms of physics teachers. Therefore, this study aims to investigate the effect of rational-emotive behavior therapy (REBT) on stress management among secondary school physics teachers. A randomized controlled group trial design was used, and the sample population comprised 64 physics teachers who served as participants. Pretest, posttest, and follow-up data were collected using the Job Stress Questionnaire (α=.73). The results showed that participants undergoing REBT experienced a significantly greater reduction in work- related stress compared to those in the control group. The findings of this study were expected to contribute to the knowledge base in measurement, counseling, and physics education. In addition, the incorporation of REBT programs was recommended to assist physics teachers in effectively managing their work-related stress.